Akuntansi Pertanggungjawaban dalam Penilaian Kinerja Pusat Biaya pada PLTM SION 2X5MW di Parlilitan (Jurnal Akuntansi Nommensen, 2023)
This study aims to determine the application of responsibility accounting in assessing cost centre performance at the SION 2x5MW MHP in Parlilitan. The research method used is descriptive method. From the results of the study it is known that the application of responsibility accounting has not gone well, because some of the requirements of responsibility accounting, namely the separation of controllable costs and uncontrollable costs, have not been applied in the preparation of the budget, so that the costs prepared by the company are not efficient and have not made the classification of account codes. PLTM SION 2x5MW also does not compare budget and realisation, performance assessment is measured from the timeliness of workmanship and cost.